Alcohol supply as a favour for a friend: Scenarios of alcohol supply to younger friends and siblings. (26th June 2019) - Lam, Tina; Ogeil, Rowan P.; Fischer, Jane; Midford, Richard; Lubman, Dan I.; Gilmore, William; Chikritzhs, Tanya N.; Liang, Wenbin; Lenton, Simon R.; Aiken, Alexandra; Allsop, Steve
Abstract: Issues addressed: Adolescents under the legal purchase age primarily source their alcohol through social networks. This study assessed the provision context from the perspective of both underage recipients and their suppliers who were older peers and siblings. Methods: Interviewer‐administered surveys were conducted with 590 risky‐drinking (50 g alcohol per session, at least monthly) adolescents. Participants of legal purchase age (18‐ to 19‐year‐olds; n = 269) reported their provision to 16‐ to 17‐year‐olds under eight scenarios. Those aged 14‐17 (n = 321) reported receipt of alcohol under the same scenarios plus two parental supply contexts. Results: Purchase‐age participants reported supply: to an underage friend (67%), an acquaintance (44%) or a sibling (16%) to drink at the same party; to a friend (43%) or sibling (20%) to take to another party (20%) and to a stranger near a bottle shop (5%). Supply to a friend at the same party was more likely if money was exchanged (60% vs 40%; P  < 0.001). Almost all (98%) 14‐ to 17‐year‐olds reported receiving alcohol from an adult (including 36% from a parent for consumption away from the parent), with a similar pattern of receipt scenarios as those reported by the 18‐ to 19‐year‐olds. Conclusions: Provision of alcohol was more frequent with a friend than a sibling or stranger, in close environmental proximity, and if money was exchanged. So what?: As supply may be sensitive to monetary considerations, the incidence of underage receipt may be affected by community‐wide pricing measures. Traditional alcohol availability regulations should be supplemented by strategies relating to the social nature of supply and demand.